CONTENT OF THE SCIENCE CURRICULUM FOR CHILDREN WITH PROBLEMS IN MENTAL DEVELOPMENT AND REQUIREMENTS FOR STUDENTS' EDUCATION - Zamira Mukhammadqulovna Jurayeva (Modern American Journals, 2025)
The article highlights the content of the natural science curriculum for children with intellectual development disorders and the requirements for students’ knowledge in this process. The pedagogical foundations of organizing the educational process are presented, taking into account students’ individual abilities, as well as their perception, memory, and thinking characteristics.
Keywords: Special education, natural sciences, curriculum, intellectual disability, individual approach, knowledge requirements.